Analysis of the intrahepatic ductular reaction and progenitor cell responses in hepatitis C virus recurrence after liver transplantation - Prakoso, E.; Tirnitz-Parker, Nina; Clouston, A.; Kayali, Z.; Lee, A.; Gan, E.; Ramm, G.; Kench, J.; Bowen, D.; Olynyk, John; McCaughan, G.; Shackel, N. (John Wiley & Sons, Inc., 2014)
Fibrosis in livers with hepatitis C virus (HCV) recurrence after liver transplantation (LT) can be rapidly progressive, and the mechanisms underlying this process are poorly understood. In livers with HCV infections in the non-LT setting, there is a significant relationship between the development of structures known as the ductular reaction (DR), hepatic progenitor cells (HPCs), and fibrosis. This study characterizes the DR, HPCs, and fibrosis associated with HCV recurrence after LT. Immunohistochemistry and confocal microscopy were used to characterize the DR, HPC, and fibrosis in liver biopsy specimens. Key findings were confirmed in a separate, independent cohort. The initial characterization cohort had 194 biopsy samples from 105 individuals with HCV recurrence after LT. The immunophenotype, morphology, and location of the DR were consistent with an HPC origin. The DR correlated with intrahepatic fibrosis (rs = 0.529, P<0.001) and the number of activated hepatic stellate cells (HSCs; rs = 0.446, P<0.001). There was an early occurrence of hepatocyte replicative arrest as well as increased hepatocyte proliferation that correlated with the DR (rs = 0.295, P<0.001). Replicative arrest preceded hepatocyte proliferation in early-stage injury. Hepatocyte proliferation decreased with advanced fibrosis; in contrast, the extent of the DR and the number of activated HSCs continued to increase. In the second cohort of 37 individuals, the DR and the number of HPCs similarly correlated with fibrosis and inflammation after LT. In conclusion, this is the first characterization of the DR in HCV-associated liver injury after LT. There was a significant correlation between the DR and the development of progressive fibrosis in HCV recurrence. These results suggest a pivotal role for both the DR and the HPC responses in the aggressive fibrosis seen with HCV recurrence after LT.